BAS/BSCR19 Visualising inflamed atherosclerotic plaques: molecular imaging using MRI and targeted ultrasmall superparamagnetic particles of iron oxide. Issue 17 (26th August 2010) - Chan, J; Monaco, C; Bhakoo, K; Gibbs, R G J
Abstract : Introduction: There are currently no clinical imaging techniques available to assess the degree of inflammation associated with atherosclerotic plaques. This study aims at visualising and characterising atherosclerosis using targeted ultrasmall superparamagnetic particles of iron oxide (USPIO) as an MRI probe for detecting inflamed endothelial cells and inflamed atherosclerotic plaques. Method: The in vitro study consists of detection and characterisation of inflammatory markers on activated endothelial cells by immunocytochemistry and anti-E-selectin antibody-conjugated USPIO. The ex vivo stage involves characterisation of inflammatory markers on human atherosclerotic plaques. Results: We have established an in vitro cellular model of endothelial inflammation induced with tumour necrosis factor α. We have confirmed the inflammation of endothelial cells with both immunocytochemistry and MRI. We can also image the inflammation of human atherosclerotic plaques by ex vivo MRI. Conclusion: We successfully developed an in vitro model to detect and characterise inflamed endothelial cells by immunocytochemistry and MRI. We can also image the inflammation of human atherosclerotic plaques by ex vivo MRI. This will allow us to develop agents and protocols for imaging vascular inflammation in atherosclerosis in the future. This pilot study will form the basis for a translational study to provide clinicians with a novel tool for in vivo assessment of atherosclerosis.